Armenian Experience in the Usage of Stratagems (General Overview) - Nazaryan, Hayk (YSU Journal of International Affairs, 2024)
Chinese, Greek, and Roman examples of the use of stratagems are known from the history of the Ancient World. The leaders, especially those experienced in military fields, used various tricks to achieve their goal. There are well-known examples of the use of stratagems in the Armenian military art, the use of which is an opportunity to ensure success in achieving numerical and technical superiority of the enemy. We often encounter actions that distract the enemy’s attention, make an unexpected attack and cause panic, blocking. There are memorable examples of strategies from the history of military operations in 1991- 1994: similar technologies were used during the liberation of Shushi, Karvachar, Sanasar, Akna. The possession of strategic skills and their proper use in military operations and operations of local importance can be of great importance for achieving your own goals, bending the advantage of another person in your favor and, of course, the successful conduct of military operations. In this sense, a deep and comprehensive study of the field, identification, development, systematization of effective experience with a positive result can be useful for future achievements.